(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This study investigates the complex stylistic challenges encountered in translation processes, examining both theoretical frameworks and practical difficulties in preserving stylistic features across languages. The research analyzes how different approaches to translation affect stylistic equivalence, with particular focus on the integration of linguistic theory, literary analysis, and practical translation strategies. The study identifies key stylistic problems in contemporary translation practice, including the preservation of rhetorical devices, adaptation of culture-specific metaphors, maintenance of author’s voice, and effective rendering of genre-specific stylistic features across linguistic and cultural boundaries.